International urban agendas and sustainable integrated urban development in developing countries - Tobias Kühner; Carlos Vinícius da Silva Pinto; Cláudia Naves David Amorim (Cidades, Comunidades e Território)
Due to the rapid and unrestrained growth of urbanization worldwide since the second half of the twentieth century, the global community is confronted with a broad spectrum of challenges. In response, the request for more sustainable cities developed in recent decades. Urban agenda setting, like the foundation of the UN-Habitat, emerged subsequently in the public policy process to countervail the negative impacts of the progress, especially in developing countries. The article wants to provide the reader with a brief introduction to global urban agendas in general and the New Urban Agenda (NUA) in specific, especially how they approach urban challenges. The analysis offers an overview of the context of the implementation of urban agendas and definitions of sustainability in its setting. Furthermore, it is examined, how non-binding doctrinaire documents like the NUA should be implemented on the regional and national levels. The challenges in implementing these urban agendas, the definition of sustainable urban agendas, and common international challenges are deconstructed and compared with the guiding principles of the NUA. The research question highlights potential approaches, how to improve the implementation of these agendas, and contributes to reducing the research gap of the global south in this regard. Therefore, as a case study, a closer look at the exemplary situation of the developing country Brazil, the local urban evolution, planning policies, and the local challenges are undertaken. To conclude, the challenges of the new urban era identified will be briefly reflected and possible pathways through alternative mechanisms, recommended by the NUA and other international guidelines, pointed out to foster implementation to the detriment of traditional local hard policy mechanisms.